The impact of public spending on water, sanitation and hygiene (WASH) adoption: Governance thresholds for complementary policies - Elvis Dze Achuo; Simplice Asongu (African Governance and Development Institute (AGDI), 2024)
Despite the global resolve to ensure the availability and sustainable management of water and sanitation, several people across the world still have very limited or no access to basic drinking water, sanitation and hygiene (WASH) services. Therefore, this study primarily examined the effect of public spending on WASH adoption. The moderating role of governance quality in the nexus among public spending and WASH adoption was equally assessed. The underlying relationships for a global panel of 45 countries over the 2000-2022 period are unravelled with the help of the system Generalised Method of Moments, Driscoll-Kraay robust standard errors and the generalised least squares estimation techniques. Results from various approaches show that public spending has a statistically significant negative effect on WASH adoption. Moreover, the interactive regressions show that public spending negatively interacts with governance to produce a negative net effect of -0.319. The underlying negative effects are apparent when some governance thresholds are exceeded. These thresholds are critical points that when reached, complementary policies are needed in order to maintain the unconditional positive effect of public spending on WASH adoption. It follows that the complementarity between public spending and governance is a sufficient and necessary condition for the promotion of WASH adoption exclusively below certain governance thresholds. Contingent on the empirical results, policymakers are advised to tailor public spending to more conveniently target local-based WASH initiatives in order to limit bureaucracy and broadbased policies. Besides, the local population should be endowed with the ability to sanction elected officials when WASH measures are not effectively implemented. Beyond the economic and political governance consideration related to WASH, institutional governance should also be improved at the local level, to the extent that ensuring the respect of interactions between the citizens and the State in the promotion of WASH is also enforced at the local level.
Keywords: 330; Public spending; Drinking water; Sanitation; Hygiene; Governance quality; WASH adoption